World Englishes Awareness among ELL and Its Implications for Language Teaching - Wahyu Nurul Fitri; Ilmi Pratiwi Rasjid; Irnawati Muhajir; Amri Muammar; Saiful .; Nur Qalbi (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This RESEARCH aims to explore postgraduate students' awareness of World Englishes (WE) and its implications for English teaching in Indonesia. There are 5 Postgraduate of English Education students from the University of Muhammadiyah Makassar participated in semi-structured interviews exploring their understanding of world englishes, attitudes toward English varieties, and teaching orientations. The results showed that most students understood WE as a diverse English language, encompassing variations in accent, vocabulary, and grammatical structures that reflect the socio-cultural contexts of users. Students generally accepted non-native English varieties and emphasized intelligibility over accent uniformity or native speaker standards, although some still considered British and American English as ideal models. Pedagogically, students with higher WE awareness tended to adopt inclusive teaching approaches, value linguistic diversity, and emphasize effective communication. These findings emphasize the importance of integrating WE into teacher education to support teaching practices that are contextualized, inclusive, and aligned with global English usage.